Utilizing Relay Points to Improve the Truckload Driving Job - Melton, Kerry Dale; Ingalls, Ricki (International Journal of Supply Chain Management, 2012)
We propose a relay point based approach on a highway transportation network to obtain robust solutions for the truck driver turnover and driver retention problem. We exploit the characteristics of the driver routing problem and truckload freight moved over a highway transportation network and introduce a new approach to route drivers over shorter distances and to move trailers continuously while considering important performance measures as related to the truck driver, transportation carrier, and customer. The amount of time drivers spend driving and the time spent at home are exploited to determine a balance between driver home time and driver pay. A mixed integer quadratic program is introduced to determine where relay points should be more optimally located to exchange equipment, perform equipment maintenance, access resting facilities, etc. while considering important costs related to transporting truckload freight. The intention is to propose a method to improve the truckload driving job but not at the expense of the transportation carrier and customer. We discuss some of the desirable characteristics of this approach and also investigate the solutions via a numerical case study.